DNA Barcoding of Shark and Ray Species from Bawean and Masalembu Waters East Java - Joesidawati, Marita Ika; Nursalim, Nining; Kholilah, Nenik; Wibowo, Marandi Eko; Cahyani, Ni Kadek Dita (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract   Highlight Research DNA Barcoding and Species Analyzed: Tissue samples from 11 individuals across five shark species and two ray species were analyzed using DNA barcoding. The species include Sphyrna lewini, Carcharhinus sealei, Stegostoma fasciatum, Galeocerdo cuvier, Carcharhinus falciformis, Rhynchobatus australiae, and Rhina ancylostoma. Genetic Similarity and Divergence: Results showed high genetic similarity within species, but some divergence was observed between different populations, indicating potential evolutionary or geographic separations. Phylogenetic Relationships: The phylogenetic analysis revealed seven distinct clades, providing insight into the evolutionary relationships of these species. Conservation Implications: Several species identified in the study are protected, such as lewini, G. cuvier, and C. falciformis. The study underscores the importance of incorporating genetic diversity data into conservation strategies to protect these ecologically vital species in Indonesia.     Abstract Sharks and rays, as apex predators or mesopredators, help maintain marine biodiversity and ecosystem balance. Their ecological and economic value underscores the need for conservation, as they face threats from overfishing, habitat loss, and climate change, with many classified as vulnerable or endangered by the IUCN. This study investigates the genetic diversity and phylogenetic relationships of sharks and rays in Bawean and Masalembu Waters, East Java, using morphological identification and DNA barcoding. The specimens were obtained from fishermen operating in Bawean and Masalembu Waters     . A total of 11 samples were analyzed from five shark species: Sphyrna lewini, Carcharhinus sealei, Stegostoma fasciatum, Galeocerdo cuvier, and Carcharhinus falciformis, and two ray species: Rhynchobatus australiae and Rhina ancylostoma. Results showed high genetic similarity within species, with some divergence observed between samples from the Bawean and Masalembu regions. For instance, populations of Sphyrna lewini from the two regions exhibited slight mitochondrial DNA sequence variations, indicating possible adaptations to local environmental conditions. Similarly, genetic differences in Rhynchobatus australiae suggest limited gene flow between populations, likely influenced by geographical barriers or habitat preferences. Phylogenetic analysis revealed seven distinct clades, highlighting evolutionary relationships such as the close grouping of S. lewini and G. cuvier, which suggests recent divergence. Several species identified, including S. lewini, G. cuvier, and C. falciformis, are protected, underscoring the need for stricter conservation and monitoring efforts to safeguard shark and ray populations. This study highlights the urgency of integrating genetic diversity into conservation strategies to ensure the long-term survival of these vital species.